1987
DOI: 10.1104/pp.84.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Thermal Properties of Thylakoid Polar Lipids of Nerium oleander L. in Relation to Chilling Sensitivity

Abstract: The polar lipid classes from thylakoids of Nerium oleander L. were studied with the aim of relating chanes in their composition and thermal behavior with reported changes in the transition temperature of their polar lipids and chilling sensitivity of their leaves. With an increase in growth temperature, the tranition temperature of phosphatidylglycerol increased from 16°C to 26°C, and for sulfoquinovosyldiacylglycerol from 19°C to 24°C. Transitions in the other lipid chsses were below -10°C for plants grown at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…This involves enzymes that tailor lipids in order to ensure optimal mobility for membranous molecules, and hence optimal efficiency of the membrane-associated photosynthetic processes [36,42]. It was recognized that the overall fluidity of the membrane cannot be simply predicted from the saturated fatty acid contents and phase transition temperatures of the component lipids [43]. Membrane fluidity also depends largely on lipid composition.…”
Section: Membrane Fluidity and The Lipid-protein Interfacementioning
confidence: 99%
“…This involves enzymes that tailor lipids in order to ensure optimal mobility for membranous molecules, and hence optimal efficiency of the membrane-associated photosynthetic processes [36,42]. It was recognized that the overall fluidity of the membrane cannot be simply predicted from the saturated fatty acid contents and phase transition temperatures of the component lipids [43]. Membrane fluidity also depends largely on lipid composition.…”
Section: Membrane Fluidity and The Lipid-protein Interfacementioning
confidence: 99%
“…Raison and Orr, 1990). The primary event which is physical in nature and temperature dependent is related to the temperature of the transition of polar Iipids and greatly influenced by the proportion ofhtm fraction of PG (Raison and Wright 1983;Murata and Yamaya, 1984;Orr and Raison 1987) and correlated with the critical temperature for photosynthesis (Hodgson et al 1987;Raison and Brown, 1989). Measurements of the phase transition temperature and critical temperature for photosynthesis when applied for comparison of closely related species, as in the case of three altitudinal ecotypes of the Licopersicon hirsutum enabled to state that all these ecotypes are chilling sensitive (Raison and Brown, 1989).…”
Section: Chilling Sensitivity Versus Response To Chillingmentioning
confidence: 99%
“…2, 3). Previous studies had also indicated the transition is more likely the solidification of a mixture of some high-and low-melting-point lipids (Raison and Wright 1983;Orr and Raison 1987). The most likely high-melting-point components in the mixture which solidifies at the transition temperature would be some of the saturated molecular species of PG and SQDG which, for oleander, have transition temperatures within the range 19 ~ to 26 ~ C , and for the few chilling-sensitive, tropical, plants studied, the range is 29 ~ to 32~ (Murata and Yamaya 1984).…”
Section: Discussionmentioning
confidence: 96%
“…Polar lipids of oleander and cucumber thylakoids were extracted, purified and separated into individual classes as described by Orr and Raison (1987). The amount of galactolipids was estimated by sugar analysis (Roughan and Batt 1968) and that of phospholipids by phosphorus analysis (Ames 1966).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation